Nonlinear Polarization Effects in Dielectrics with Hydrogen Bonds; Russian Physics Journal; Vol. 61, iss. 4 - Kalytka V. A. Valery Aleksandrovich; Korovkin M. V. Mikhail Vladimirovich; Mekhtiyev (Mekhtiev) A. Ali; Yurchenko A. V. Aleksey Vasilievich (2018, 2018)
Title screen